Stochastic Frontier Analysis as a Tool for Evaluating the Effectiveness of Banks Lending To the Real Economic Sectors in Ukraine - Baranova, V.; Kots, G.; Matarneh, R.; Lyashenko, V. (Everant Publisher, 2016)
This work focuses on the fluctuations of rating values of the bank lending efficiency in the real sector of the economy. The analysis is carried out on a sample of banks in Ukraine within the period from 2015 to 2016 years. To examining the values of bank lending efficiency in the real sector of Ukraine’s economy, the article considers the efficiency stochastic boundary model, which is use the intermediary function for bank functioning description based on the asset approach. The forms of distribution by particular efficiency value levels of bank lending in the real sector of Ukraine’s economy had been analyzed in detail. Results have revealed the tendency to increase in average values of bank lending efficiency in the real sector of Ukraine’s economy. This is observed against the background of a reduction the number of banks and an actual lending to the real sector of the economy. At the same time it is shown that of bank lending efficiency the real sector of Ukraine’s economy is determined in many respects a balanced deposits-loans system.
Keywords: stochastic efficiency boundary; loans; deposits; efficiency level